61.4k views
3 votes
6.8x+9.3= -9.4+3.4(2-5x)

User Rick Moss
by
4.4k points

2 Answers

2 votes

Answer: the answer to this is x=0.5

Explanation:

In order to solve this you have to combine the multiplied terms into a single fraction so its going to look like this - 34x/5 + 9.3= -9.4+3.4(2-5x)

The reposition your terms and put together your multiplied terms into a fraction,Once you have that done distribute them

Subtract 9.3 on both sides.you may simplify and then multiply all the terms with the same value to get rid of the denominators from the fractions

also add 85x to both sides then finally divide both side by the same term which get you -59.5/119 and then simplify and you get -0.5

so x= -0.5

User Jcrudy
by
4.6k points
2 votes

Answer:

x=-0.5

Explanation:

step 1

6.8x+9.3=-9.4+3.4(2-5x)

6.8x+9.3=-9.4+(3.4)(2)+(3.4)(-5x) distribute

6.8x+9.3=-9.4+6.8+-17x

6.8x+9.3=(-17x)+(-9.4+6.8) combine like terms

6.8x+9.3=-17x+-2.6

6.8x+9.3=-17x-2.6

step 2

add 17x to both sides.

6.8x+9.3+17x=-17x2.6+17x

23.8x+9.3=-2.6

step 3

subtract 9.3 from both sides.

23.8x+9.3-9.3=-2.6-9.3

23.8x=-119

step 4

divide both sides by 23.8

23.8x/23.8= -11.9/23.8

The answer is =-0.5

User Anibal
by
4.4k points